Real-time line drawing of 3D models taking into account curvature-based importance - Wada, Shohei (2019)
In recent years, many line drawing algorithms have been proposed for 3D shape depiction. One common drawback is that these algorithms draw only part of the necessary lines for fully depicting the shape. Cole et al.1) have shown that these algorithms can be complementary to each other. Based on that, in this paper, we combine the previous algorithms to produce better line drawings of 3D objects. By directly superposing multiple line drawing algorithms, however, there is a risk of generating too many unnecessary lines, especially in regions where many lines are located near to each other, making them to appear over-sketched. To solve this problem, we define an attribute called “importance” for all points on each line. The importance describes which lines should be drawn in preference. In addition, we determine the width of the lines based on the number of lines in their neighborhood. Our algorithm runs on GPU, achieving real-time speed. From experimental results, our method avoids drawing excessive lines while conveying the shapes effectively.